Poškodbe orbite - Kansky, Andrej (Zdravniški vestnik, 2002)
Background. Orbit is involved in 40% of all facial fractures. There is considerable variety in severity, ranging from simple nondisplaced to complex comminuted fractures. Complex comminuted fractures (up to 20%) are responsiblefor the majority of complications and unfavorable results. Orbital fractures are classified as internal orbital fractures, zygomatico-orbital fractures, naso-orbito-ethmoidal fractures and combined fractures. The ophtalmic sequelae of midfacial fractures are usually edema and ecchymosis of the soft tissues, subconjuctival hemorrhage, diplopia. iritis, retinal edema, ptosis, endophthalmos, ocular muscle paresis, mechanical restriction of ocularmovement and nasolacrimal disturbances. More severe injuries such as optic nerve trauma and retinal detachments have also been reported. Within thewide range of orbital fractures small group of complex fractures causes most of the sequelae. Therefore identification of severe injuries and adequatetreatment is of major importance. The introduction of craniofacial techniques made possible a wide exposure even of large orbital wall defects and their reconstruction by bone grafts. In spite of significant progress, repair of complex orbital wall defects remains a problem even for the experienced surgeons. Results. In 1999 121 facial injuries were treated at ourdepartment (Clinical Centre Ljubljana Dept. Maxillofacial and Oral Surgery). Orbit was involved in 65% of cases. Isolated inner orbital fracturespresented 4% of all fractures. 17 (14%) complex cases were treated, 5of them being NOE, 5 orbital (frame and inner walls), 3 zygomatico-orbital, 2FNO and 2 maxillo-orbital fractures. Conclusions. Final result of the surgical treatment depends on severity of maxillofacial trauma. Complex comminuted fractures are responsable for most of the unfavorable results and ocular function is often permanently damaged (up to 75%) in these fractures.
Keywords: Diagnosis; Eye injuries; Izid zdravljenja; kosti; Očesne poškodbe; oftalmologija; oko; Orbital fractures; Orbitalni zlomi; poškodbe; Surgery; therapy; Treatment outcome; zdravljenje; zlomi